2017
DOI: 10.1002/bem.22043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local vibration and pulsed electromagnetic field on bone fracture: A comparative study

Abstract: The effectiveness of various therapeutic methods on bone fracture has been demonstrated in several studies. In the present study, we tried to evaluate the effect of local low-magnitude, high-frequency vibration (LMHFV) on rat tibia fracture in comparison with pulsed electromagnetic fields (PEMF) during the healing process. Mid-diaphysis tibiae fractures were induced in 30 Sprague-Dawley rats. The rats were assigned into groups such as control (CONT), LMHFV (15 min/day, 7 days/week), and PEMF (3.5 h/day, 7 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Ten (Butezloff et al, 2015;Cheung et al, 2012;Chow et al, 2011;Chung et al, 2014;Leung et al, 2009;Shi et al, 2010;Wehrle et al, 2015;Wehrle et al, 2014;Wei et al, 2016) of the nineteen studies adopt a 20 min/d treatment, four (Bilgin et al, 2017;Komrakova et al, 2013;Stuermer et al, 2014;Stuermer et al, 2010) In this review, vibration regimes with a magnitude lower than 1 ×g were regarded as LMHFV and those with a magnitude greater than 1 ×g were regarded as HMHFV (high magnitude high frequency vibration). Six (Butezloff et al, 2015;Komrakova et al, 2016;Komrakova et al, 2013;Stuermer et al, 2014;Stuermer et al, 2010;Usui et al, 1989) of the included studies use HMHFV and twelve (Bilgin et al, 2017;Cheung et al, 2012;Chow et al, 2011;Chung et al, 2014;Gao et al, 2016;Leung et al, 2009;Shi et al, 2010;Wehrle et al, 2015;Wehrle et al, 2014;Wolf et al, 2001) adopt LMHFV. One study uses both LMHFV and HMHFV (Uchida et al, 2017).…”
Section: Search Criteriamentioning
confidence: 97%
See 4 more Smart Citations
“…Ten (Butezloff et al, 2015;Cheung et al, 2012;Chow et al, 2011;Chung et al, 2014;Leung et al, 2009;Shi et al, 2010;Wehrle et al, 2015;Wehrle et al, 2014;Wei et al, 2016) of the nineteen studies adopt a 20 min/d treatment, four (Bilgin et al, 2017;Komrakova et al, 2013;Stuermer et al, 2014;Stuermer et al, 2010) In this review, vibration regimes with a magnitude lower than 1 ×g were regarded as LMHFV and those with a magnitude greater than 1 ×g were regarded as HMHFV (high magnitude high frequency vibration). Six (Butezloff et al, 2015;Komrakova et al, 2016;Komrakova et al, 2013;Stuermer et al, 2014;Stuermer et al, 2010;Usui et al, 1989) of the included studies use HMHFV and twelve (Bilgin et al, 2017;Cheung et al, 2012;Chow et al, 2011;Chung et al, 2014;Gao et al, 2016;Leung et al, 2009;Shi et al, 2010;Wehrle et al, 2015;Wehrle et al, 2014;Wolf et al, 2001) adopt LMHFV. One study uses both LMHFV and HMHFV (Uchida et al, 2017).…”
Section: Search Criteriamentioning
confidence: 97%
“…No clinical study was found, based on our search criteria on publications prior to the 12 th March 2017. Among the fifteen rat studies, one uses males (Bilgin et al, 2017). Among the other fourteen studies on female rats, five (Chow et al, 2011;Komrakova et al, 2016;Komrakova et al, 2013;Stuermer et al, 2014;Wei et al, 2016) report vibration treatment on ovariectomised (OVX) rats, five (Butezloff et al, 2015;Cheung et al, 2012;Chung et al, 2014;Shi et al, 2010) apply vibration to both OVX and sham-OVX models and one to both OVX and non-OVX rats (Stuermer et al, 2010).…”
Section: Search Criteriamentioning
confidence: 99%
See 3 more Smart Citations